The Implementation of The Internet of Things in The Duck Egg Incubator Monitoring System - Yanti Yanti; Abd Rohman; Siti Maesaroh; Asep Mustopa; Rizki Muh Febrian (TIERS Information Technology Journal, 2022)
Internet of Things (IoT) is a technology that creates modernization and makes it easier for humans to carry out their activities. IoT can be used in various fields, especially in monitoring stand-alone devices. This technology can communicate with other devices by utilizing radio waves and data transmission formats. This study aims to apply IoT to the duck egg incubator monitoring system. The method was an experimental method of designing a temperature and humidity monitoring system by implementing IoT. NodeMCU ESP8266 was used as the microcontroller and the DHT22 sensor was used as the temperature and humidity sensor. This study successfully implemented an IoT system in a duck egg incubator. The test results showed that temperature and humidity data can be read on the blynk application on a smartphone. Temperature and humidity in the incubator can be monitored in real time so that the process of monitoring the performance of the duck egg incubator becomes easier and more practical. This is very useful in increasing the efficiency and effectiveness of the device’s performance.